Kinetic Modelling of the Thermal Degradation of Bioactive Compounds During Pasteurization Process in Tomato Juice - Kurniawati, Ajeng Dyah; Faizah, Faizah; Dwi Pratiwi, Evia Zunita (Journal of Applied Food Technology, 2025)
Juice ranks among the most favored beverage products globally. Consumption of tomato juice is acknowledged as a functional food which provides advantages for several mechanisms in the body. Tomato juice is often processed using the pasteurization method to extend its shelf life and inhibit deterioration during storage and distribution. The negative aspects of the pasteurization process in tomato juice processing are the degradation of beneficial components due to increased temperatures. This research aimed at determining the kinetic characteristics of vitamin C and its antioxidant activity in tomato juices throughout the pasteurization process, including the reaction rate constant as a function of process temperature. This research examined the impact of temperature on the degradation of carotenoids, vitamin C, and the reduction of antioxidant activity in pasteurized tomato juice at temperatures ranging from 60 to 90 °C. The pasteurization process significantly decreased the concentrations of vitamin C, carotenoids, and antioxidant activity (P < 0.05) in tomato juice. The degradation kinetics of bioactive compound in pasteurized tomato juice is followed first-order kinetic with the R2 > 0.90, and Arrhenius models could explain the changes in the rate of constant degradation in each of the bioactive compounds. Vitamin C was the most thermolabile compound in pasteurized tomato juice.